OnTrackNY's learning healthcare system. Issue 4 (6th April 2020) - Humensky, Jennifer L.; Bello, Iruma; Malinovsky, Igor; Nossel, Ilana; Patel, Sapana; Jones, Genevra; Cabassa, Leopoldo J.; Radigan, Marleen; Sobeih, Tarek; Tobey, Caroline; Basaraba, Cale; Scodes, Jennifer; et al.
Abstract: Worldwide, early intervention services for young people with recent-onset psychosis have been associated with improvements in outcomes, including reductions in hospitalization, symptoms, and improvements in treatment engagement and work/school participation. States have received federal mental health block grant funding to implement team-based, multi-element, evidence-based early intervention services, now called coordinated specialty care (CSC) in the USA. New York State's CSC program, OnTrackNY, has grown into a 23-site, statewide network, serving over 1800 individuals since its 2013 inception. A state-supported intermediary organization, OnTrackCentral, has overseen the growth of OnTrackNY. OnTrackNY has been committed to quality improvement since its inception. In 2019, OnTrackNY was awarded a regional hub within the National Institute of Mental Health-sponsored Early Psychosis Intervention Network (EPINET). The participation in the national EPINET initiative reframes and expands OnTrackNY's quality improvement activities. The national EPINET initiative aims to develop a learning healthcare system (LHS); OnTrackNY's participation will facilitate the development of infrastructure, including a systematic approach to facilitating stakeholder input and enhancing the data and informatics infrastructure to promote quality improvement. Additionally, this infrastructure will support practice-based research to improve care. The investment of the EPINET network to build regional and national LHSs will accelerate innovations to improve quality of care.